Staged management of open Lisfranc injury: Experience from 14 patients. Issue 17 (April 2017) - Gu, Wenqi; Shi, Zhongmin
Abstract : Abstract: There are still controversies on the management and outcome of open Lisfranc injury in available studies. This study evaluates the staged management of Lisfranc injury and its complications. Patients who received a staged strategy for open Lisfranc injury were reviewed. One patient with degloving injury suffered from partial skin and hallux necrosis which was treated by debridement, hallux amputation, definitive internal fixation, and local flap transfer on the 12th day after first stage management. A definitive internal fixation and simultaneous skin graft or flap coverage were performed in another 3 patients with soft tissue defects. Other patients without soft tissue problems underwent a second stage of definitive internal fixation. Bone union was observed on the 12.5th week after definitive surgery. The median AOFAS midfoot score at the last follow-up was 74.4 ± 8.7, while the average VAS score was 2.2 ± 1.8. The average return-to-work time was 8th months postoperatively in 9 patients. Flap necrosis, infection, implant failure, nonunion, and osteomyelitis were not observed during the follow-up. Two patients received Lisfranc arthrodesis for persistent pain due to posttraumatic arthritis. In the management of open Lisfranc injury, surgeons must consider soft tissue condition. Staged strategy is a rational protocol for this severe injury. Temporary K-wire fixation after early radical debridement and realignment will facilitate the definitive internal fixation until soft tissue condition improves, which also can decrease the soft tissue complication.